TRANSLATION OF “PENGERTIAN BAHASA DAN ASPEK BAHASA” INTO ENGLISH USING ANALYSIS OF TEXTUALITY FROM THE VIEW OF TEXT CENTRE COHESION AND COHERENCE - Agus Juriadi (Humanitatis : Journal of Language and Literature, 2019)
This paper analyzes a translated text by comparing of work of the two participants in translating source language into target language by seeing its pros and cons viewed from he main core of text ; coherence and cohesion. The analyses cover the strengths and the drawbacks of each translator work. The strengths focused on the elements of coherence and cohesion, while the drawbacks are mapped through the communicative competence; grammatical competence, sociolinguistic competence, discourse competence and strategic competence. At the end of the paper the writer serves the recommendation for each of the translator dealing with the work he/she has done. In general, the work of translation text much depends on how the translator prepares himself with 1) a knowledge of source language knowledge, target language knowledge, text-type knowledge, domain language, and contrastive knowledge each of the above, 2) an inference mechanism which permits :a) the decoding of texts, i.e reading and comprehending source language texts, b) the encoding of texts i.e writing the target language texts, and 3) communicative competence; four areas of knowledge and skills namely grammatical competence, sociolinguistic competence, discourse competence, and strategic competence. At last, a good translation is called coherence when the all elements of the text works to frame it and a text is achieving its cohesion means that the text is also coherence.